Improving Personal Problem-Solving Skills Through Resource Therapy: A Psychological Approach for the Community - Hardani Widhiastuti; Dini Anggraheni; Fitri Nurmasari (SWAGATI : Journal of Community Service, 2026)
Indonesian migrant workers abroad are vulnerable to emotional stress, anxiety, and difficulties in social and cultural adaptation, which can affect their psychological well-being. This community service activity aims to introduce Resource Therapy (RT) as a psychological approach to help participants recognize and utilize their internal resources in dealing with personal problems. The program was conducted at the Consulate General of the Republic of Indonesia (KJRI) in Penang, Malaysia, involving 36 participants comprising 30 Indonesian migrant workers and 6 KJRI staff members. The methods used included participatory psychoeducation, interactive discussions, self-reflection exercises, and practice in identifying positive psychological resources. Evaluation was conducted through participant engagement observation, reflective discussions, and post-activity feedback focusing on emotional awareness, self-reflection, and perceived usefulness of the intervention. The results showed that participants understood the basic concepts of Resource Therapy and could identify internal resources to cope with personal and emotional problems. This program has the potential to become a culturally relevant, community-based psychoeducational service model that can be replicated in Indonesian migrant worker communities in other countries.